Penerapan K3 ( Keselamatan dan Kesehatan Kerja ) Pada Karyawan Pabrik Kripik Tuntungan Dalam Upaya Mencegah Kecelakaan Kerja - Yughni Aulia Nabila; Nurdiana Tanjung; Sandiyatun Daulay; Abdurrozzaq Hasibuan (Lembaga Pengembangan Kinerja Dosen, 2024)
Occupational Health and Safety (K3) are the steps we take to create a healthy and safe work environment, with the aim of reducing the possibility of work accidents or illnesses due to negligence which can result in decreased work enthusiasm and productivity. In accordance with the Basic Health Law of the Republic of Indonesia no. 9 of 1960 Part I Article II, Occupational Health refers to health conditions which aim to ensure that workers obtain an optimal level of health physically, spiritually and socially, through efforts to prevent and treat diseases or health problems caused by work, the work environment , as well as general illnesses. This research was conducted in two stages using a descriptive survey method which included field surveys and observations of the environment and work processes. The aim of this research is to prevent work accidents among chip factory workers. Although employees have implemented OSH efforts in the workplace, there is still room for further improvement in the long term.